Effect of eco-enzyme application on soil nutrient and plant productivity of green mustard-peanut in inceptisol - Rachman, Idris Abd; Umasugi, Buhari; Aji, Krishna; Hakim, Nurul Fahira A; Sofyan, Adnan; Hasan, Asrul Dedy Ali (Kultivasi, 2025)
Appropriate land management has a long-term impact on soil performance and is believed to improve soil fertility. This study investigated the effect of eco-enzymes on soil nutrients and plant productivity of green mustard-peanut in inceptisol. The research was conducted from February to April 2025.  The experiment used a randomized block design (RBD) consisting of 5 treatments and replicated 3 times, so that there were 15 units, including N0 = without Eco-enzyme, N1 = Eco-enzyme 2cc/L. N2= Eco-enzyme 4cc/L, N3= Eco-enzyme 6cc/L, and N4= Eco-enzyme 8cc/L. The commodities used were green mustard (Brassica juncea L) and peanut (Arachis hypogaea Linn). Soil properties variables included soil pH, N-total, and P-available, while plant productivity variables included plant height, number of leaves, leaf area, fresh weight, and pod production. The results showed that the concentration of eco-enzymes had a significant effect on N-total, P-available, green mustard plant height, and peanut plant height. However, eco-enzyme concentration had no significant effect on soil pH, number of green mustard leaves, green mustard fresh weight, green mustard leaf area, number of peanut branches, and peanut pod production. The lowest production of green mustard was 0.85 tons/ha, and the highest was 3.29 tons/ha. While the lowest production of Peanut pods was 4.3 tons/ha and the highest was 6.67 tons/ha.